A multi-band MIMO antenna system with coupled-fed modified rectangular patch elements for 5G systems - Radwa Khalil Hamad; Amira Ibrahim Zaki; Mohamed Mohamed Omar; Marwa H. Sharraf (Advances in Computing and Engineering, 2022)
A four-port multiple input multiple output (MIMO) antenna system constructed of four compact dual-band (38/60 GHz) microstrip patch antennas is proposed for 5G mobile applications. Each individual element is optimized to achieve the desired performance of the overall MIMO system. Numerical and experimental investigations are achieved to assess the performance of both the single-element antenna and the four-port MIMO antenna system. It is shown that the simulation results agree with the experimental measurements, and both show good performance of the proposed MIMO antenna system. The bandwidths achieved around 38 GHz and 60 GHz are about 2 GHz and 3.2 GHz, respectively. The performance of the MIMO antenna system including the return loss at each antenna port and the coupling coefficients between the different ports are investigated. The radiation patterns produced when each port is excited alone are shown to be suitable for spatial diversity scheme. They have a high radiation efficiency exhibited by a balloon-like shaped radiation pattern for both the upper and lower frequency bands. It is shown that the envelope correlation coefficient (ECC) and the diversity gain (DG) are suitable for performance for the targeted 5G bands.